Analyzing Contemporary Project Management Issues of FoxMeyer's ERP System Failure - Nurul Khairisha Afza Khairuddin,; Nur Ain Mohd Ariffin,; Muhammad Daniel Amir Md Zaihan,; Siti Zulaikha Md Latif,; Nur Diyanah Nabilah Jaffar,; Mohamad Aizi Salamat, (Applied Information Technology And Computer Science, 2023)
In FoxMeyer's Enterprise Resource Planning (ERP) System Failure, modern project management concerns are examined through the lens of one of the failed companies, which was a $5 billion business that ranked as the country's fourth-largest distributor of pharmaceuticals and had the technology to increase productivity. The main focus of the conversation is how FoxMeyer's project has several problems, as identified by the Project Management Body of Knowledge (PMBOK) that affect the project management and ultimately lead to project failure. The study indicated that the scope of the FoxMeyer project was risky. They needed software that could manage a high volume of transactions and complex pricing algorithms. Furthermore, one of the procedures for locating, gaining access, assessing, and controlling the risk exposures to losses is risk management for the FoxMeyer project. In this instance, the companies failed to identify and mitigate the risks associated with the ERP's adoption. In the conclusion of FoxMeyer’s case, this project needs a proactive approach to project management. It can be solved by changing the circumstances, maintaining an open line of communication, and being responsible for emerging risks.